"For a splendid cause": Irish missionary nuns at home and on the mission field, 1921-1962 - Lynch, Kate (2012)
In the years following Ireland's political independence in 1922 the popularity of its missionary movement was unprecedented. This most Catholic of endeavours helped to assert Ireland's difference from Britain. Religious women actively participated in this process. Their medical work and subsequent representations of the mission fields contributed to a rhetoric of Irish nationalism that served to define postcolonial Ireland within a universal, Catholic discourse. However, the location of their missionary spaces, largely in British colonial Africa, brought the sisters into contact with the empire from which Ireland had recently withdrawn. In their encounters with local people, the sisters perpetuated a form of colonialism that will be studied as a seeming contradiction to the Catholic Church's stance against British rule in Ireland. This is conducted through the lens of gender, and exposes the variation in Catholic-informed ideals of femininity in this postcolonial period of Ireland's history. To study these nuns is to explore the gendered and uneven power relations within the Church, their contribution to the expansion of Catholicism and their ambiguous role in empire. By drawing on the scalar connections between varied missionary spaces including the body, convent and domestic home, in both Ireland and Tanganyika, this thesis contributes to broader debates in historical geography and postcolonial theory.